GAMBARAN STATUS KESEHATAN GIGI DAN MULUT SISWA TUNAGANDA TINGKAT SD DAN SMP DI SLBG YAYASAN BHAKTI MITRA UTAMA BALEENDAH KABUPATEN BANDUNG - Nindya Apsari (Poltekkes Kemenkes Bandung, 2023)
Children with special needs are children who have physical, mental, intellectual, social and emotional limitations. Multiple disabled children are children who experience more than one limitation, where these limitations can become an obstacle in maintaining healthy teeth and mouth. This study aims to determine the index of dental and oral hygiene, as well as the index of caries experience in children with special needs who have multiple disabilities (deaf and mentally retarded). This type of research is descriptive. The study population was dual students (deaf and mentally retarded) at the elementary and junior high school levels at the Bhakti Mitra Utama Foundation, Baleendah Special School, Bandung Regency. The research sample was taken using a total sampling technique with a total sample of 11 people. After that, the resulting data is processed and presented in the form of a frequency distribution table. The results showed that the index of dental and oral hygiene in elementary school respondents as much as 4 out of 6 respondents had poor OHI-S criteria (36.3%). Meanwhile, at the junior high school level, 3 out of 5 respondents had moderate OHI-S criteria (27.3%). The caries experience index for primary and junior high school respondents is included in the low criteria, which is 1.9. The caries experience index of primary teeth for primary school level respondents as many as 4 out of 6 respondents had a bad def-t index (66.7%).